Visoes da transiçao - Cardoso, Fernando HenriqueLula (1945-) (Documentos)
v. 1. Sen. Fernando Henrique Cardoso, Dep. Fed. Guilherme Afif Domingos, Sen. Jarbas Passarinho -- v. 2. Dep. Fed. Luiz Inacio Lula da Silva, Sen. Marco Maciel, Dep. Fed. Roberto Freire, Gov. Waldir Pires.